Analisis Nilai Perusahaan dari Segi Keputusan Investasi, Struktur Modal, dan Kinerja Keuangan (Studi Kasus Pada Perusahaan Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia periode 2015-2019) - Gendro Wiyono; Agus Dwi Cahya; Diany Damayanti (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine the effect of investment decisions, capital structure, and financial performance on company value carried out in the food and beverage sub-sector companies listed on the IDX for the 2015 - 2019 period. This study took samples from companies in the food and beverage sub-sector with a total population of 26 companies. The technique used in sampling is purposive sampling. Based on these techniques obtained a sample of 12 companies. Based on the results of the partial test research, investment decisions have no significant effect on firm value, capital structure has a significant effect on firm value, and financial performance has a significant effect on firm value. Meanwhile, based on the simultaneous test, the investment decision variables, capital structure and financial performance have a significant effect on firm value. Keywords : investment decisions, capital structure, financial performance, and firm value